Health education and clinical care of immigrant women with female genital mutilation/cutting who request postpartum reinfibulation. Issue 1 (October 2016) - Abdulcadir, Jasmine; McLaren, Sophie; Boulvain, Michel; Irion, Olivier
Abstract: Objective: To evaluate the percentage of women with female genital mutilation/cutting who request postpartum reinfibulation, and to assess outcomes after specific care and counseling. Methods: A retrospective review was undertaken of consecutive medical files of immigrant women with FGM/C who attended a center in Geneva, Switzerland, between April 1, 2010, and January 8, 2014. The number of postpartum reinfibulation requests and outcomes were assessed. If a patient requests postpartum reinfibulation despite receiving detailed information and counseling, a longer follow-up is arranged for further counseling. Results: Among 196 women with FGM/C, 8 (4.1%) requested postpartum reinfibulation. All eight were of East African origin, had FGM/C type III, and received a longer and more targeted follow-up than did those who did not request reinfibulation. After at least 1 year of follow-up, none of the eight was willing to undergo reinfibulation. One woman who attended the clinic only once during her first pregnancy consulted the emergency ward of the study center 3 years later because of postcoital bleeding following infibulation performed in her home country a few months after her second delivery in Switzerland. Conclusion: Specific care and counseling for women with FGM/C type III can improve the acceptability of defibulation without reinfibulation.